The historical dimension of the poetics of Ricardo Palma fiction - Valenzuela Garcés, Jorge (2019)
This article intends to answer certain questions related to the poetics of the fiction of Ricardo Palma: What did he think about fiction as an act of imagination and fantasy? What implications did he consider fiction as an instrument that linked him to the documentary record and the past? What did Palma show in hisTraditions regarding the relationship between fiction, history, and memory? The poetics of the fiction of Palma and its popular character are emphasized. We use as a theoretical framework the proposals of Ana María Amar Sánchez in her book "El relato de los hechos".